Use of remote sensing in control of good agricultural and environmental conditions on agricultural farms - Pluto-Kossakowska, Joanna; Osińska-Skotak, Katarzyna; Fijałkowska, Anna; Chmiel, Jerzy (Ecological Questions, 2013)
In the frame of EU common agricultural policy, applicant farmers shall receive subsidies for agricultural production. A producer receiving payments is required to meet the basic requirements for the maintenance of all farmland in good agricultural conditions consistence with environmental protection. Since 2009, applicant farmer is obliged to comply with standards adopted by Poland in the so-called cross-compliance requirements. Member States shall determine at the national level for Good Agricultural and Environmental Conditions (GAEC). Compliance with these standards, to maintain good agricultural practice is controlled selectively in the annual inspection campaigns conducted by the Agency for Restructuring and Modernization of Agriculture (ARMA). One of control method is Control with Remote Sensing (CwRS), method that involves the determination in satellite or aerial images boundaries of areas subject to subsidies. Experience in the use of remote sensing, however, indicate the potential for the use of processed satellite or air orthophotomaps not only for cropping delineation but also to verify certain elements of agricultural practices. During the CwRS routine, one could indicate a possible non-compliance issues directly on the image and thereby optimize the process of control. The studies indicated which of the requirements to maintain land in good agricultural conditions might be monitored with CwRS. The results of the series of experiments showed that both kind of aerial and satellite orthophoto can be consider as equivalent materials. Features or phenomenon spread over a large area or occurred point-wise are detectable in image easier than during field inspection. Also wherever access or visibility on the ground is limited due to the morphology complexity, road network, etc., orthophotomap provide better angle of view. Nevertheless, the ratio benefit/cost for managing the entire control on national level should be checked against the efficiency of field control.